A finite state model for a self-help system based on minhaj 'al Abidin - Othman, Roslina; Nordin, Mohamad Fauzan; Zeki, Akram M. (Medwell Publishing, 2016)
Finite state models even though very traditional can also be applied to the analysis and design of both abstract and physical systems. A general finite state model has been developed and applied to a self help system to assess the initial state of the user and discern the ways that the user can transit from that state to higher states ultimately progressing to reach a certain goal. The general model has also been diversified to show, how it can be used to add different features to the system. A proto type system entitled self-help maqam-based search system based on the seven maqams or hurdles mentioned in the book Minhaj 'al Abidin has been used as a use case. In this book, Minhaj 'al 'Abidin by Imam Ghazzali (RA), it has been illustrated how a man by crossing seven distinct hurdles one at a time by achieving certain knowledge and performing specific deeds, one can gain bounties of Allah (SWT) at the end.